An analysis of the current position regarding anti-dumping law and procedures in South Africa - Gillespie, Marie-Lou (Department of Public Law, 2021)
In order to correctly assess the current status of antidumping law in South Africa, as well as to determine the role that it will play in the future, it is necessary to take its historical setting into account . This requires an investigation into the origins of South African anti-dumping law and the manner in which it was applied in the past.· In this regard the economic and political conditions which prevailed in the past are relevant as is the way in which these conditions have changed. As will become evident there has been much change regarding anti-dumping law in South Africa. This process of transition, concerning the status and role of anti-dumping law, must be recognised as forming the background when analysing the current position of anti-dumping law in South Africa. To determine a way forward for the law relating to dumping, in a manner that takes these economic and political changes accurately into account, and which is of a nature that is practically workable for South Africa, it is desirable to ref er to other legal systems and how these legal systems have used and developed their anti-dumping law.